« Homosexualiser » un rituel chrétien. Le Fêtez-Dieu de l’association David & Jonathan - Mickaël Durand (Genre, Sexualité et Société)
The literature on gay and lesbian Christians focuses on the process of identity negotiation between their religious and sexual identifications. The means fostering this process, however, such as the religious practices proposed by gay or inclusive Churches and organizations, have been understudied. This article deals with a specific ritual of the Parisian group of the organization David & Jonathan: the Fêtez-Dieu. This ritual is neither a traditional rite nor a practice pertaining to “secular forms of religiosity.” Based on ethnographical observations and in-depth interviews with members of the organization David & Jonathan, this article shows how the Fêtez-Dieu articulates a religious socialization and a homosexual socialization, thus encouraging the process of identity tension reduction. The criticisms addressed to the Fêtez-Dieu nonetheless reveal that the ritual operates through different modes of appropriation. Finally, the article aims at contributing to the analysis of homosexual socialization and religious modernity.